Research Status in Clinical Practice Regarding Pediatric and Adolescent Bipolar Disorders - Liu, Lu; Meng, Ming; Zhu, Xiaotong; Zhu, Gang (Frontiers in Psychiatry, 2022)
Bipolar disorders (BP) have a high morbidity. The first onset of 27.7% of bipolar disorders is before 13 years old and 37.6% is between 13–18 years old. However, not all of the pediatric and adolescent bipolar disorder patients receive therapy in time. Therefore, studies about pediatric and adolescent disorders have aroused increased attention in the scientific community. Pediatric and adolescent bipolar disorder present with a high prevalence rate (0.9%–3.9%), and the pathogenic factors are mostly due to genetics and environment, however, the pathological mechanisms remain unclear. Pediatric and adolescent bipolar disorders manifest differently from adult bipolar disorders and the use of scales can be helpful for diagnosis and treatment evaluation. Pediatric and adolescent disorder patients have been confirmed to have a high comorbidity rate with many other kinds of disorders. Both medication and psychological therapy have been shown to be safe and efficient methods for the treatment of BP. This review summarizes the research status related to the epidemiology, pathogenic factors, clinical manifestations, comorbidities, diagnostic and treatment scales, medications, and psychological therapies associated with bipolar disorders.